Disease activity, steroid use and extraintestinal manifestation are associated with increased disability in patients with inflammatory bowel disease using the inflammatory bowel disease disability index: a cross-sectional multicentre cohort study. Issue 10 (October 2018) - Lo, Bobby; Julsgaard, Mette; Vester-Andersen, Marianne Kajbæk; Vind, Ida; Burisch, Johan
Abstract : Background: The inflammatory bowel disease disability index (IBD-DI) was developed recently. The aim was to translate the IBD-DI into Danish and validate it for future clinical studies and practice, and to assess the level of disability among IBD patients. Patients and methods: The IBD-DI was translated using a transcultural adaptation method. Between January and December 2017, patients from three outpatient clinics in three different regions in Denmark were given the final version of the IBD-DI for self-completion. Validation was carried out according to guidelines. Disability level was assessed among the entire cohort and in various subgroups. Results: A total of 200 patients were included in the study, including 112 Crohn's disease (CD) and 88 ulcerative colitis (UC) patients. The response rate was 90%. The IBD-DI showed excellent reliability and validity. CD patients showed worse disability levels than UC patients [mean (SD): CD: 37.3 (20.2) vs. UC: 21.7 (16.4); P =0.04]. In both CD and UC, significantly increased disability levels were found between patients with active disease, use of steroid and extraintestinal manifestation ( P <0.05). Conclusion: A valid and reliable version of the IBD-DI is now available in Danish for future studies. Several clinical factors are shown to affect the levels of disability among patients with CD and UC. The disability levels are significantly increased in patients with active disease, treated with systemic steroids, and extraintestinal manifestations are present in both CD and UC. Further testing of the Danish IBD-DI is needed to assess its responsiveness and interpretability. Abstract : Supplemental Digital Content is available in the text.